2010
DOI: 10.1063/1.3357292
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of crystalline domain size and epitaxial orientation of CdTe/Si(111) quantum dots

Abstract: We have investigated the crystalline configuration of CdTe quantum dots ͑QDs͒ grown on hydrogen passivated Si͑111͒ substrates by hot wall epitaxy. Coplanar and grazing incidence diffraction were used for determination of dot strain state and the vertical and lateral dimensions of the crystalline domain. A change in aspect ratio was observed as a function of dot size. X-ray diffraction ͑XRD͒ results show that despite a mismatch of almost 20% the islands grow with a fairly good epitaxial orientation with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
(23 reference statements)
0
10
0
Order By: Relevance
“…We performed the experiment growing CdTe films onto polymeric substrates (Kapton, Dupont) by hot wall deposition technique in high-vacuum (~10 −7 Torr). This growth technique has been chosen for its simplicity and for being demonstrated to yield high quality CdTe films with properties similar to films produced by molecular beam epitaxy 28 , 29 . Substrate temperature was set to T = 150 °C, and source temperature to 510 °C, yielding a growth rate F = 14.0(3) nm /min.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…We performed the experiment growing CdTe films onto polymeric substrates (Kapton, Dupont) by hot wall deposition technique in high-vacuum (~10 −7 Torr). This growth technique has been chosen for its simplicity and for being demonstrated to yield high quality CdTe films with properties similar to films produced by molecular beam epitaxy 28 , 29 . Substrate temperature was set to T = 150 °C, and source temperature to 510 °C, yielding a growth rate F = 14.0(3) nm /min.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Experimental methods. -CdTe (5N) was evaporated on Si(001) substrates by HWE, a well-controlled and highly reproducible growth technique [20,21]. The experimental HWE setup is described in detail in Ref.…”
mentioning
confidence: 99%
“…As in the case of (Zn,Mn)Te/ZnSe QDs, described by Sellers et al 8 , the expected type II band alignment of CdTe/Si system would increase the carriers radiative life-time facilitating the formation of MPs. We have already shown that despite the big lattice mismatch around 19%, almost perfect CdTe QD can be grown on Si(111) 9 . The big advantage of using Si substrates is its compatibility with most processes used by the semiconductor industry.…”
Section: Introductionmentioning
confidence: 97%